Innovating democracy: democratic theory and practice after the deliberative turn - Goodin, Robert E. (New Delhi, 2012)
In recent years democratic theory has taken a deliberative turn. Instead of merely casting the occasional ballot, deliberative democrats want citizens to reason together. They embrace 'talk as a decision procedure'. But of course thousands or millions of people cannot realistically talk to one another all at once. When putting their theories into practice, deliberative democrats therefore tend to focus on 'mini-publics', usually of a couple dozen to a couple hundred people. The central question then is how to connect micro-deliberations in mini-publics to the political decision-making processes of the larger society. In Innovating Democracy, Robert Goodin surveys these new deliberative mechanisms, asking how they work and what we can properly expect of them. Much though they have to offer, they cannot deliver all that deliberative democrats hope. Talk, Goodin concludes, is good as a discovery procedure but not as a decision procedure. His slogan is, 'First talk, then vote'. Micro-deliberative mechanisms should supplement, not supplant, representative democracy. Goodin goes on to show how to adapt our thinking about those familiar institutions to take full advantage of deliberative inputs. That involves rethinking who should get a say, how we hold people accountable, how we sequence deliberative moments and what the roles of parties and legislatures can be in that. Revisioning macro-democratic processes in light of the processes and promise of micro-deliberation, Innovating Democracy provides an integrated perspective on democratic theory and practice after the deliberative turn.
Keywords: Democracy